2018
DOI: 10.3748/wjg.v24.i11.1206
|View full text |Cite
|
Sign up to set email alerts
|

Three-microRNA signature identified by bioinformatics analysis predicts prognosis of gastric cancer patients

Abstract: AIMTo identify multiple microRNAs (miRNAs) for predicting the prognosis of gastric cancer (GC) patients by bioinformatics analysis.METHODSThe original microarray dataset GSE93415, which included 20 GC and 20 tumor adjacent normal gastric mucosal tissues, was downloaded from the Gene Expression Omnibus database and used for screening differentially expressed miRNAs (DEMs). The cut-off criteria were P < 0.05 and fold change > 2.0. In addition, we acquired the miRNA expression profiles and clinical information of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…In addition, Pan et al (34) highlighted that the expression levels of miR-374 were decreased in glioma tissues and were associated with the prognosis of glioma patients, which is consistent with the results of the present study. It has been reported that the aberrant expression of certain miRNAs is associated with the development of cancer via the abnormal regulation of multiple BPs and signaling pathways (35). To further elucidate the molecular function of miR-374a and its target genes, functional enrichment analyses of the target genes in GO terms and KEGG pathways were performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pan et al (34) highlighted that the expression levels of miR-374 were decreased in glioma tissues and were associated with the prognosis of glioma patients, which is consistent with the results of the present study. It has been reported that the aberrant expression of certain miRNAs is associated with the development of cancer via the abnormal regulation of multiple BPs and signaling pathways (35). To further elucidate the molecular function of miR-374a and its target genes, functional enrichment analyses of the target genes in GO terms and KEGG pathways were performed.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-23b-3p was downregulated in colon cancer and mediated tumor metastasis by regulating FZD7 and MAP3K1 [57]. In addition, studies also found that miR-23b-3p was upregulated in GC tissues [58]. Previous studies indicated that miR-130a-3p was downregulated and inhibited cancer in many cancers [59][60][61][62].…”
Section: Discussionmentioning
confidence: 98%
“…Potential targets of miR-4429 were predicted based on TargetScan and miRDB databases. 18 WT-FOXM1 and Mut-FOXM1 plasmids were constructed. ME-180 and C33A cells were seeded into a 24-well plate at 5×10 3 per well, and transfected when their confluency reached 90%.…”
Section: Luciferase Reporter Gene Assaymentioning
confidence: 99%